2010
DOI: 10.3941/jrcr.v4i4.360
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted coil embolization of a wide-necked renal artery aneurysm

Abstract: We present a case of stent-assisted coil embolization of a wide-necked renal artery aneurysm performed at our institution. The technique involved a stent being delivered over the neck of the aneurysm. Subsequently a catheter was placed into the aneurysm through the stent mesh and the aneurysm was then filled with detachable coils. Complete aneurysm occlusion was obtained and there was no evidence to suggest renal infarction on a follow-up contrast CT scan 6 months later. Our preliminary experience suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 13 publications
0
15
0
10
Order By: Relevance
“…It is strongly suggested that aneurysms larger than 2 cm in size and all pseudoaneurysms should be treated due to the risk of lethal rupture of the sac, especially in women of childbearing age. However, true aneurysms less than 2 cm have a negligible risk of complications, and thus authors advise a follow-up with yearly imaging [1,4]. While the Rundback type I aneurysm is a candidate for treatment with a covered stent, Rundback type II and III aneurysms likely can be man- aged by the other techniques.…”
Section: Discussionmentioning
confidence: 97%
“…It is strongly suggested that aneurysms larger than 2 cm in size and all pseudoaneurysms should be treated due to the risk of lethal rupture of the sac, especially in women of childbearing age. However, true aneurysms less than 2 cm have a negligible risk of complications, and thus authors advise a follow-up with yearly imaging [1,4]. While the Rundback type I aneurysm is a candidate for treatment with a covered stent, Rundback type II and III aneurysms likely can be man- aged by the other techniques.…”
Section: Discussionmentioning
confidence: 97%
“…18 Estudos com o tratamento endovascular desses aneurismas são restritos a casuísticas pequenas ou relatos de caso. [19][20][21][22][23] Antoniou e Antoniou 24 apresentaram revisão de 22 aneurismas tratados com uso de stents, com 91% de sucesso técnico e 27% de complicações menores, como a oclusão de pequenas artérias polares. Durante o seguimento de 8 meses, foi relatada uma reestenose da artéria renal.…”
Section: Tabela 2 Detalhes Técnicos Das Correções Endovasculares De Aunclassified
“…Nesses casos, a utilização de técnicas de remodelamento com uso de stent, associada ao uso de molas, ou de molas e cola, é fundamental para a preservação dos vasos nativos e o correto selamento do aneurisma. 2,4,9,15,20 Quanto aos aneurismas do tipo III, que emergem a partir de pequenas artérias segmentares e suprem uma pequena parte do parênquima renal, podem ser embolizadas com a oclusão do vaso nutridor. Agentes líquidos, como a cola e o Onyx ® (Ev3 Inc., Plymouth, Estados Unidos), podem ser usados para esse propósito.…”
Section: Tabela 2 Detalhes Técnicos Das Correções Endovasculares De Aunclassified
“…The number of cases diagnosed has been increasing because of wider use of imaging methods such as Doppler ultrasonography and computed tomography angiography (CTA). 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
“…Indications for treatment and choice of technique are still controversial because of the small number of studies available, which is a consequence of the rarity of the disease, making it difficult to conduct randomized clinical trials. 2 , 3 Open surgery is one treatment option, with excision of the aneurysm and reconstruction or nephrectomy. 2 As endovascular techniques evolved, treatment of RAA using percutaneous repair became possible, offering reduced surgical trauma, shorter postoperative hospital stay, and lower morbidity, when compared to open surgical treatment.…”
Section: Introductionmentioning
confidence: 99%